A potência do imaginário e a democracia no pensamento de Cornelius Castoriadis - Silva, Manoel Binoni Bandeira da (Universidade do Vale do Rio dos Sinos, 2023)
The proposition of this dissertation is to analyze the theoretical construct of the philosopher Cornelius Castoriadis, on the importance of the imaginary in the formation of humanity and in the constitution of society. In this path, the imaginary also focuses on the creation and emergence of different forms of social management, but mainly on the generation of the democratic regime. Another relevant aspect is the approach to the role of the imaginary power on the constitution of the psyche and the development in the formation of the singular psyche, as well as the configuration of the collective psyche and the emergence of the social-historical. The central goal of this research is to understand the reach of the imaginary power in the creation of the totality of meanings and the incidence to propitiate transformations in democracy. The methodology used in this investigation is, essentially, a bibliographic review. The study reaffirms that all creations of humanity are forged by the power of the imaginary and the power of imagination is imagination itself. Still, it´s possible to say that society and, consequently, the social individual, are in a continuous movement of transformation due to the incidence of the radical imaginary and the instituting imaginary. Therefore, the democratic institution, being unfinished, can be improved to guarantee the collective participation of the members of society so that they can create their own laws. Castoriadis believes in direct democracy as an ideal model of social participation, as it gives management power to all members of society.
Keywords: Potência imaginária; Imaginário; Psique; Sociedade; Democracia; Imaginary power; Imaginary; Psyche; Society; Democracy; ACCNPQ::Ciências Humanas::Filosofia